Recovery of Two Replication-Competent Canine Distemper Viruses That Separately Express Dabie Bandavirus Gn and Gc - Lin, Jiahui; Li, Yuehua; Lyu, Liangpeng; Wang, Qianqian; Zhang, Hui; Ni, Bo; Liu, Fuxiao (Frontiers in Veterinary Science, 2022)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne zoonosis with a high mortality rate in humans. Additionally, dogs are frequently reported to be infected with this disease. There has been no commercially available vaccine for humans and animals as yet. The SFTS is caused by Dabie bandavirus (DBV), formerly known as SFTS virus. The DBV is now classified into the genus Bandavirus in the family Phenuiviridae. DBV Gn and Gc can induce specific immune responses in vivo. In this study, we used reverse genetics technique to construct two recombinant canine distemper viruses (rCDVs), rCDV-Gn and -Gc, which could express Gn and Gc in vitro, respectively. Both of the recombinants, derived from a common parental CDV, were independently subjected to twenty serial passages in cells for Sanger sequencing. Neither point mutation nor fragment deletion was found in the Gn open reading frame (ORF), whereas the rCDV-Gc showed a nonsynonymous mutation (A157C) in the Gc ORF, correspondingly resulting in a mutation of amino acid (T53P) in the Gc. Growth curve of the rCDV-Gc almost coincided with that of a wild-type CDV, but exhibited a significant difference from that of the rCDV-Gn. Much research remains to be performed to demonstrate whether both recombinants are able of inducing specific immune responses in vivo.